Hepatoprotective Effect of Silymarin Peptide on Carbon Tetrachloride-Induced Acute Liver Injury in Mice - Ananda; Tsend-Ayush Damba; Xiulan Su; Khurelbaatar Nyamdavaa (Central Asian Journal of Medical Sciences)
Objective: Liver diseases and injuries are significant global health concerns; in particular, acute liver injury (ALI) is a prominent cause of liver diseases and is associated with high morbidity and mortality. The application of natural products in preventing and treating liver diseases is considerable. Silymarin and silymarin peptides derive from the Milk thistle (Silybum marianum). Still, they differ in their composition and effects: Silymarin is a complex mixture of flavonoids, primarily made up of silybinin, silybinin, and silychristin. Silymarin is well-known for its antioxidant, anti-inflammatory, and hepatoprotective properties. It is often a dietary supplement to support liver health. Silymarin Peptide refers to specific peptides derived from silymarin. These peptides have more enhanced bioavailability and activity of effect compared to the whole silymarin compound. Therefore, this study aimed to investigate the hepatoprotective effects of silymarin peptide on acute liver injury (ALI) in mice induced by carbon tetrachloride (CCl4) compared with Silymarin. Methods: Forty-eight male C57BL/6J mice were randomly divided into six groups (n=8 per group): Control group: regular saline+olive oil, Negative control group: 10% CCl4 solution (10 μl/g), Treatment group 1: CCl4+50 mg/kg silymarin peptide, Treatment group 2: CCl4+100 mg/kg silymarin peptide, Treatment group 3: CCl4+200 mg/kg silymarin peptide, and Positive control group: CCl4+100 mg/kg silymarin. The treatment of silymarin was used as a positive control. At the end of the experiments, mice were euthanized, and the blood and liver samples were collected. Results: The results showed that silymarin peptide ameliorated the histopathological damage of liver tissues caused by CCl4 and decreased the CCl4-induced serum AST and ALT levels, among which the 200 mg/kg dose demonstrated the most notable protective effect. Additionally, silymarin peptide showed no significant influence on CCL2 levels but markedly reduced TNF-α and CXCL5 levels, with the most apparent impact at 100 mg/kg. Finally, the terminal deoxynucleotidyl transferase‐mediated dUTP‐nick end labeling (TUNEL) staining indicated that the 200 mg/kg dose of silymarin peptide restrained CCl4-induced hepatocytic apoptosis. Conclusion: Silymarin peptide alleviated CCl4-induced ALI in mice by inhibiting inflammatory cytokines release and decreasing hepatocyte apoptosis.